Technology transfer in developing countries - Mahmoud, Omer; Khalifa, Othman Omran; Hassan Abdalla Hashim, Aisha; Saeed, Rashid Abdelhaleem; Hameed, Shihab Ahmed (2011)
Technology has a great effect on productivity, wealth, health and life style of individuals and countries. Due to the rapid growth of technologies and poor infrastructure in developing countries they feel that they are far behind developed countries and Technology transfer has become a great issue of concern for researchers, companies and policy makers. However, the technology transfer is very challenge process that contains enormous barriers and constrains such as lack of infrastructure and educational development of the people. One of main challenges faced by Technology transfer is to have a clear process by which to identify the most suitable technology from out of several alternative technologies. This paper present and discusses technology, transfer process, channels, challenges and barriers.